Recovery of muscular skeletal tissues after injury - Renström, P. (2001)
The muscular skeletal system undergoes qualitative changes after an injury, in response to decreased levels of physical activity and prolonged rehabilitation. After injury, as a result of inactivity, the bone structure in athletes may become decalcified and weaker , with an increased risk of fracture. Inactivity can lead to bone resorption and depress bone formation whereas bone that has been exposed to regular exercise adapts to the increased demand by increased bone formation. Articular cartilage is affected by inactivity, as the water and proteoglycan content decrease. With immobilization, the cartilage becomes soft and fragmented, the chondrocytes die in increasing numbers, the collagen fibers split and fibrillate, and the bone under the cartilage demineralizes. These changes are probably reversible, but after eight weeks of immobilization they may be permanent. The best way to keep articular cartilage in good condition is gentle exercise. Muscle tissue quickly loses quality and volume, even after a short period of inactivity due to injury. The proportion of functional loss is greater than the loss in muscle mass or volume, and both of the latter two are greater than the loss of extremity circumference. The main reason for the greater decrease in muscle function compared with the cross-sectional area may be due to nerve-related factors. With regular exercise, muscle increases in size. The healthy active muscle structure protects the joints from injury by improving the distribution of forces. Tendons hypotrophy as a result of inactivity after injury. The tensile strength, elasticity and total weight of the tendon tissue decrease, while the collagen fibers become thinner and disoriented. The cross-links become smaller and reduced in number. Early motion and regular exercise improves both the mechanical properties and the structural properties (breaking strength) of the tendon. Interestingly enough, overload and eccentric exercise have been shown to improve healing potential in tendinopathy. Ligaments are affected by injury and inactivity in the same way as tendons. Regular exercise improves the mechanical and structural properties. In summary, the effects of inactivity and immobilization after injury can be devastating. Early motion and loading are important after injury. Activity is beneficial for all tissues of the body. A well-planned rehabilitation program, with as much activity and early motion as possible, is the best course for a speedy recovery.